Pemberantasan Mafia Tanah dengan Menggunakan Instrumen Hukum di Indonesia (Peraturan Menteri Agraria dan Tata Ruang/Badan Pertanahan Nasional Nomor 16 Tahun 2020) - Hanafiyah Arya Nashuha; Muh. Afif Mahfud (UNES Law Review, 2023)
The land mafia periodically reviews the steps taken to avoid land disputes and conflicts, but in reality these actions are always illegal. One aspect of implementation is that the event must be organized, planned and executed by a group of individuals. In reality (das sein) there are many land mafias in Indonesia where this can result in land disputes due to legal actions carried out by these individuals through land mafia intermediaries. The aim of this research is to determine the eradication of the land mafia using Indonesian legal instruments. The research carried out is a normative juridical research type. Documentary/library research is used to collect data, especially by examining documents closely related to the criminal activities of the Land Mafia and obtaining information in the form of formal provisions and existing data. The results of the research show that through the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 16 of 2020 concerning the Organization and Work Procedures of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, Directorate General VII, Directorate General of Land and Land Acquisition, has a very important role in efforts to eradicate the land mafia in Indonesia. Land mafia refers to illegal activities such as forgery of documents, land misappropriation, extortion, and corruption in land transactions. Keyword: Mafia, Land, Certificates, Laws, Ministerial Regulations.